Respuestas

2014-02-19T05:28:10+01:00

sen (2u) = 2 sen(u) cos (u) 
cos (2u) = cos^2 u - sen^2 u = 2 cos^2 u - 1 = 1 - 2 sen^2 u 

Ahora 
cos (30º) = √3/2 

cos (30º) = 2 cos^2 15º - 1 

2 cos^2 15º = 1 + cos(30º) = 1 + √3/2 = (2 + √3)/2 

cos 15º = (1/2) *√(2 + √3) 
----------------------------------- 
cos (30º) = 1 - 2 sen^2 15º 
2 sen^2 15º = 1 - cos 30º = (2 - √3)/2 
sen 15º = (1/2) *√(2 - √3) 
----------------------------------- 
Verificamos 
2 * sen 15º cos 15º = 2 * (1/2) *√(2 - √3)*(1/2) *√(2 + √3) 
= (1/2) √(2 - √3)√(2 + √3) 
= (1/2) √(4 - 3) 
= 1/2 
= sen 30º 
---------------------- 
Podemos racionalizar 
(√3 +/- 1)^2 = 1 +/- 2√3 + 3 = 4 +/- 2√3 = 2 (2 +/- √3) 
(√3 +/- 1) = √2 √(2 +/- √3) 
√(2 +/- √3) = (1/√2) (√3 +/- 1) 
√(2 +/- √3) = (√2/2) (√3 +/- 1) 

sen 15º =(√2/4) (√3 - 1) 
cos 15º =(√2/4) (√3 + 1) 

sen 15º =(1/4) (√6- √2) 
cos 15º =(1/4) (√6+ √2) 

Entonces 

tan 15º = (√6- √2)/(√6+ √2) 
racionalizamos 
tan 15º = (√6- √2)^2/(6- 2) 
tan 15º = (6 + 2 - 2√12)/4 
tan 15º = (6 + 2 - 4√3)/4 
tan 15º = 2 - √3 
---------------------------- 
De la misma forma 
cotan 15º = 2 + √3 
-------------------------- 

También 
sec 15º = 4/(√6+ √2) 
racionalizamos 
sec 15º = 4*(√6- √2)/(6-2) 
sec 15º = √6 - √2 
---------------------- 
de la misma forma 
cosec 15º = √6 + √2